2022
DOI: 10.3390/coatings12050629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Shot Peening Process on Corrosion Resistance of Aluminum Alloy: A Review

Abstract: The high humidity of marine atmosphere and the existence of corrosive chloride ions lead to the premature corrosion failure of aluminum alloy components. The development of surface-strengthening technology provides an opportunity to prolong their service life spans. As a mature surface-strengthening technology, the shot peening process is widely used, owing to its advantages over other strengthening technologies, including its easy operation and high production rate. The shot-peened surface integrity depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…By analyzing the K ads values (Table 4), it was concluded that the GSO components had the strongest affinity for adsorbing onto the C38 surface. A higher K ads value indicated a more robust and effective adsorbed layer on the metal surface, resulting in superior surface coverage [50,[53][54][55].…”
Section: Anticorrosion Performancementioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the K ads values (Table 4), it was concluded that the GSO components had the strongest affinity for adsorbing onto the C38 surface. A higher K ads value indicated a more robust and effective adsorbed layer on the metal surface, resulting in superior surface coverage [50,[53][54][55].…”
Section: Anticorrosion Performancementioning
confidence: 99%
“…By analyzing the Kads values (Table 4), it was concluded that the GSO components had the strongest affinity for adsorbing onto the C38 surface. A higher Kads value indicated a more robust and effective adsorbed layer on the metal surface, resulting in superior surface coverage [50,[53][54][55]. The inhibitory effect of natural GSO on steel corrosion at different inhibitor concentrations was investigated over a temperature range of 298 to 328 K. Polarization curves of C38 were obtained in a 1 M HCl medium before and after adding GSO at a concentration of 0.5 g/L, following a 30 min immersion time.…”
Section: Anticorrosion Performancementioning
confidence: 99%
“…The formation of a passive film on aluminum alloy surfaces is significantly related to the residual stress field. For this reason, the shot-peening method is also promising [137]. Numerous opinions being advanced in the literature indicate that technologies enabling grain refinement to nanometric sizes through strong plastic deformation can improve the corrosion resistance of aluminum alloys [138,139].…”
Section: Recent Advances and Future Perspectives For Corrosion Protec...mentioning
confidence: 99%
“…Thus far, some contradicting results have been reported regarding the corrosion behavior of shot-peened Ti6Al4V alloys. While some claim that the peening process increases corrosion resistance as a result of the modified surface structure [24,25], others assert the opposite [26]. According to Zhang et al [15], proper ultrasonic shot-peening (USSP) treatment improves the corrosion resistance of a selective laser-melted Ti6Al4V alloy in aqueous 3.5% NaCl medium, attributed to the increased microstructural defects (e.g., dislocation density) due to USSP, promoting passive film formation on the peened surface.…”
Section: Introductionmentioning
confidence: 99%